The Comparison of The Effectiveness of Mango And White Ambon Banana on Hemoglobin Levels In Trimester II Pregnant Women With Anemia - Dahlan, Febry Mutiariami; Nurkamilawati, Yuli; Aulya, Yenny; Gusti Rivandi, Affan (International Journal of Midwifery and Health Sciences, 2024)
Background: Anemia is a condition in which circulating erythrocytes and/or hemoglobin (Hb) cannot fulfill their function of providing oxygen to body tissues. More than 50% of anemia cases spread throughout the world are directly caused by insufficient iron intake. Purpose: To determine the comparison of the effectiveness of Mango and White Ambon Banana on Hemoglobin Levels in Anemic Pregnant Women in the Second Trimester at the Ciater Community Health Center, South Tangerang. Method: This research is a quasi-experimental research design with a two group pre and posttest design, a sampling technique using cluster sampling, a total sample of 30 respondents divided into two treatment groups. This research was conducted in the Ciater Community Health Center area, South Tangerang City in October 2023. The instruments used were mango fruit and white Ambon banana, observation sheet, Easy Touch Blood Hemoglobin. Data analysis used paired sample t- test and Independent T-Test Results: There is an effect of giving mangoes and white Ambon banana on hemoglobin levels in pregnant women in the second trimester at the Ciater Health Center with a p-value of 0.000. The results of the study showed that there was no difference in the average hemoglobin levels in pregnant women in the second trimester between the consumption of mangoes and white Ambon banana with a p-value of 0.292. Conclusion: The results of the study show that there is no difference in the average effect of mangoes and white Ambon banana on the hemoglobin levels of pregnant women. Suggestion: The results of this research can be put into practice independently, especially for consuming mangoes and Ambon banana to increase Hemoglobin levels.